High Performance Thin-Layer Chromatography Method for Quantification of Betulinic Acid in Extracts of Leaves of Orthosiphon stamineus Benth. - Hussain, Khalid; Ismail, Zhari; Sadikun, Amirin (Asian Journal of Chemistry, 2010)
The standardization of herbal products is challenging due to unavailability or inadequacy of analytical methods and standards. Therefore, the present study aimed to develop a single step high performance thin-layer chromatography (HPTLC) method for quantification of betulinic acid in extracts of Orthosiphon stamineus (OS). Samples having minimum interfering species and higher content of betulinic acid were prepared by chromatography of the extract over silica gel with hexane and ethyl acetate (6:4 v/v). The quantification of betulinic acid. Lowest limit of detection (LOD) and lowest limit of quantification (LOQ) were found to be 0.02 and 0.20 μg, respectively. The method had shown linearity in a range of 0.2-500 μg with correlation coefficient 0.9979. Recovery and accuracy (intra and inter day) values were found to be 96.12-97.65, 97.34- 98.84 and 97.16-98.37 %, respectively, with relative standard deviation (RSD) less than 5. Results of this study indicate that the method is sensitive, accurate and precise.